2021
DOI: 10.2196/25505
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Communication Tool (Loop) for Team-Based Care in Pediatric and Adult Care Settings: Hybrid Mixed Methods Implementation Study

Abstract: Background Communication within the circle of care is central to coordinated, safe, and effective care; yet patients, caregivers, and health care providers often experience poor communication and fragmented care. Through a sequential program of research, the Loop Research Collaborative developed a web-based, asynchronous clinical communication system for team-based care. Loop assembles the circle of care centered on a patient, in private networking spaces called Patient Loops. The patient, their ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…This study echoes the recent implementation literature underscoring the COVID-19 pandemic as an outer-setting construct inconclusively affecting implementation [ 35 - 37 ]. In fact, the pandemic may have facilitated and accelerated the technology implementation process with significant effects on CareNav characteristics, the inner setting, characteristics of the CRC staff, and the outer setting.…”
Section: Discussionsupporting
confidence: 81%
“…This study echoes the recent implementation literature underscoring the COVID-19 pandemic as an outer-setting construct inconclusively affecting implementation [ 35 - 37 ]. In fact, the pandemic may have facilitated and accelerated the technology implementation process with significant effects on CareNav characteristics, the inner setting, characteristics of the CRC staff, and the outer setting.…”
Section: Discussionsupporting
confidence: 81%
“…As cases rose, the capacity to withstand the excess call volume became difficult to maintain at the call center until more call operators and other team members were recruited and hired into their respective roles. Communication among different teams became vital to ensure stability of infrastructure, allowing for timely and prompt connections to be made utilizing a key element of feedback loops [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies focus on patients' and healthcare professionals' perceptions and preferences [24][25][26][27][28] and others on organisational factors that affect acceptance and diffusion of text-based communication. 22 23 Husain et al 22 implemented and evaluated a web-based clinical communication system for team-based care with patients with a focus on facilitators and barriers, but found that even though the system could fill a gap of communication, existing modes of communication, workflows, incentives and lack of integration with electronic medical records were barriers to adoption. Even factors such as individual tension for change among healthcare professionals to use text-based communication with patients made implementation difficult.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Even factors such as individual tension for change among healthcare professionals to use text-based communication with patients made implementation difficult. 22 Another recent study investigated parents’ usage and experiences of communicating with professionals in hospital-to-home transitions after their child’s preterm birth or surgery related to this, using an eHealth device with embedded online chat, where they could communicate with nurses at the hospital. Even though the parents felt that the eHealth device supported their self-treatment by providing communication with healthcare professionals, the authors described barriers related to the technical infrastructure and to the adoption by healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation